Now You Can Find It All on the Internet: Spelling Out Secret Knowledge in China and the Challenge of Complexity - Homola, Stéphanie (International journal of divination and prognostication, 2025)
This study examines the challenges that Chinese practitioners of divination face as their specialized knowledge becomes increasingly available online. Traditionally, diviners rely on body-based computation skills to memorize and apply complex techniques. These skills are the hallmarks of an expertise whose transmission is usually safeguarded within a personal relationship between master and disciple. However, some practitioners disclose these skills in online videos making them available to a wide audience. This work analyzes the rhetoric that practitioners develop when revealing secret knowledge to the general public in the broader context of changing modes of knowledge transmission and in contrast to other fields of traditional knowledge in China. I rely on the analysis of a video disclosing specialized skills called “Secret formulas of the palm” (shouzhang jue 手掌诀) to show how, through online dissemination, specialists of divination use complexity as a rhetorical device in the construction of their expertise.